Cetaceans in the Maldives: a review - Andersen, R. Charles; Sattar, Shahaama A.; Adam, M. Shiham (J. Cetacean Res. Manage., 2023)
The cetaceans of the Maldives were poorly known until relatively recently, but have received increased attention over the past decade. Twentythree species of cetacean have now been recorded. A number of sightings surveys, and one acoustic survey, have been completed. The species most frequently seen is the spinner dolphin (Stenella longirostris). A national system for reporting cetacean strandings has been in place since 2000, although some earlier strandings were also reported; approximately 160 strandings of 16 species have been recorded to date. The species most commonly reported stranding is the sperm whale (Physeter macrocephalus). Ambergris has been exported from the Maldives since ancient times; recent export statistics are reviewed. All cetaceans are protected by law within Maldivian waters. More significantly, most forms of net-fishing, including gill-netting and purse-seining are banned in the Maldives to protect the traditional pole and line tuna fishery. Cetacean-watching is becoming increasingly popular, with spinner dolphins being the main attraction, although other species are also sought after on specialist trips.